1996
DOI: 10.1161/01.str.27.10.1765
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke With Atrial Fibrillation

Abstract: Stroke in patients with AF is generally more severe and outcome markedly poorer than in patients with sinus rhythm. This accentuates the importance of anticoagulant treatment of individuals with AF. A lower blood pressure in the acute stage of stroke may contribute to the increased stroke severity in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
257
4
16

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(295 citation statements)
references
References 32 publications
18
257
4
16
Order By: Relevance
“…Pre-existing congestive heart failure [32][33][34] and atrial arrhythmia 32,33,[35][36][37] are well-documented risk factors for mortality after stroke, and our findings suggest a prognostic significance of these conditions in thrombolysis patients. However, in our study, the increased risk of mortality attributable to these conditions is very similar in thrombolysis and nonthrombolysis patients, suggesting that these conditions should probably not be considered contraindications to thrombolysis.…”
Section: Bateman Et Al Thrombolysis Nationwide Inpatient Samplesupporting
confidence: 54%
“…Pre-existing congestive heart failure [32][33][34] and atrial arrhythmia 32,33,[35][36][37] are well-documented risk factors for mortality after stroke, and our findings suggest a prognostic significance of these conditions in thrombolysis patients. However, in our study, the increased risk of mortality attributable to these conditions is very similar in thrombolysis and nonthrombolysis patients, suggesting that these conditions should probably not be considered contraindications to thrombolysis.…”
Section: Bateman Et Al Thrombolysis Nationwide Inpatient Samplesupporting
confidence: 54%
“…7 The Copenhagen Stroke Study (a prospective, community-based study of 1197 patients with acute stroke) demonstrated that patients with AF had a higher mortality rate (OR, 1.7; 95% CI, 1.2 to 2.5), longer hospital stays (50 days vs. 40 days, p<.001), and a lower discharge rate to their own homes (OR, 0.60; 95% CI, 0.44 to 0.85). 8 This study also demonstrated that neurological and functional outcomes were markedly poorer in patients with atrial fibrillation due to more severe strokes. 8 Vitamin K antagonists such as warfarin are highly effective in preventing stroke in patients with atrial fibrillation.…”
Section: Introductionmentioning
confidence: 61%
“…8 This study also demonstrated that neurological and functional outcomes were markedly poorer in patients with atrial fibrillation due to more severe strokes. 8 Vitamin K antagonists such as warfarin are highly effective in preventing stroke in patients with atrial fibrillation. Warfarin reduces the risk of stroke by two-thirds and mortality by one-quarter compared with control.…”
Section: Introductionmentioning
confidence: 61%
“…Cardioembolic stroke due to atrial fibrillation (AF) is a common cause of ischemic stroke and is associated with high mortality or morbidity with subsequent disability [1][2][3]. Furthermore, AF is one of the strongest predictors of in-hospital mortality among patients with acute ischemic stroke [4].…”
Section: Introductionmentioning
confidence: 99%